Perlindungan Hukum Otoritas Jasa Keuangan terhadap Investor Pasar Modal atas Diberlakukannya Delisting Saham oleh Bursa Efek Indonesia - I Dewa Gede Angga Bhasudeva; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2022)
This study aims to analyze and describe the legal consequences for issuers whose shares are delisted by the stock exchange and analyze how the legal protection provided by the financial services authorities to capital market investors for the implementation of stock delisting by the stock exchange. Capital market developments affect legal certainty and protection for investors. This research is included in normative legal research that uses a conceptual approach and legislation. Judging from the results of the research, many go public companies have not disclosed information that should be known by the public and the OJK so that these issuers will be subject to delisting sanctions by the IDX. Delisting can be granted if the issuer wants to become a closed company but is still a go public company. Shareholders are given legal protection by the OJK, namely, preventive in nature as evidenced by guidance and supervision by the OJK, repressive protection as evidenced by administrative sanctions for parties who violate the legal rules regarding the capital market in force in Indonesia.